Determinant Analysis of Non Muslim Choose PT Bank Syariah Indonesia, Tbk In Pematangsiantar - M. Fauzan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The background of this research is that the number of non-Muslim customers at PT Bank Syariah Indonesia, Tbk in Pematangsiantar continues to increase every year, in 2018 there were 641 people, in 2019 there were 810 people, in 2020 there were 1.012 people, and in 2021 totaling 1.231 people. So that with the increase in the number of non-Muslim customers, PT Bank Syariah Indonesia, Tbk in Pematangsiantar can continue to develop its business activities both in terms of raising funds, distributing funds, and services. Several factors that can be improved are promotion, product, service, and religious stimuli. The purpose of this study is to analyze how much influence promotions, products, services, and religious stimuli have on the decision of non-Muslim customers to choose PT Bank Syariah Indonesia, Tbk in Pematangsiantar either partially or simultaneously. This research method contains the type of research, research location and time, population and sample, data collection techniques, data analysis techniques with validity test, reliability test, descriptive analysis, normality test, classical assumption test, coefficient of determination test, and linear regression equation analysis. multiple. The results of this study are partially, there is a significant influence between promotions on non-Muslim decisions to choose PT Bank Syariah Indonesia, Tbk in Pematangsiantar. Partially, there is no significant effect between products on the decision of non-Muslims to choose PT Bank Syariah Indonesia, Tbk in Pematangsiantar. Partially, there is a significant influence between services on the decision of non-Muslims to choose PT Bank Syariah Indonesia, Tbk in Pematangsiantar. Partially, there is a significant influence between religious stimuli on the decision of non-Muslims to choose PT Bank Syariah Indonesia, Tbk in Pematangsiantar. Simultaneously, there is a significant influence between the variables of promotion, product, service, and religious stimuli on the decision of non-Muslims to choose PT Bank Syariah Indonesia, Tbk in Pematangsiantar.